A secure transmission method based on cooperative jamming for correlated main and wiretap channels - Sai XU; Shuai HAN; Weixiao MENG (Dianxin kexue)
A secure transmission method was proposed based on cooperative jamming to reduce the secrecy loss caused by the correlation between main and wiretap channels and to improve the secrecy.Considering that the existing methods of cooperative jamming focused on the case of independent main and wiretap channels, the achievable secrecy performance was not satisfactory.In view of this, a cooperative jamming method for correlated main and wiretap channels was proposed.Based on the model of cooperative jamming under correlated main and wiretap channels, the secrecy rate maximization under secrecy outage constraint was formulated.Then, the norm bounding approach and the Bernstein-type inequality approach were employed to approximately transform the probabilistic constraint into a deterministic form, and a safe approximate solution of beamforming vector and AN covariance matrix was obtained.Simulation results show that the proposed method can reduce the secrecy loss under high correlation.